Aerogel Spring‐Back Correlates with Strain Recovery: Effect of Silica Concentration and Aging. Issue 10 (29th July 2021) - Sivaraman, Deeptanshu; Zhao, Shanyu; Iswar, Subramaniam; Lattuada, Marco; Malfait, Wim J.
Abstract : Silica aerogels display exceptional properties and great application potential, with a mature market in thermal insulation. Both supercritical drying (SCD) and ambient pressure drying (APD) routes are implemented industrially. Herein, how aging and silica content affect the mechanical properties, and how these in turn determine the shrinkage, spring back, and density during APD are systematically investigated. The APD densities display a U‐shaped dependence of density w.r.t. silica concentration. At low silica concentrations, the gels cannot withstand the capillary forces during APD and dense xerogels are obtained. At intermediate to high concentrations, APD shrinkage is strongly reduced and density increases with silica concentration. A series of cylinders are prepared by SCD and investigated by uniaxial compression and their strain recovery is determined systematically. The mechanical responses are plastic, viscoelastic, and brittle in nature for low, intermediate, and high silica concentrations, respectively. The strain recovery of the SCD cylinders correlates to the degree of spring back during APD. The viscoelastic response of SCD aerogels having 6 wt% corresponds to the silica concentration where a minimum in APD aerogel density is observed. The importance of gel mechanics for silica aerogel spring back during APD, in addition to surface modification and hydrophobization is highlighted. Abstract : Ambient pressure drying (APD) aerogel density has U‐shaped dependence on silica content. For low silica contents, supercritical drying (SCD) aerogels do not recover mechanical strain; intermediate density aerogels recover strain after compression. Aging improves strain recovery and APD spring back at intermediate silica content. APD spring back is efficient, independent of aging time, at high silica content